Assessment of stable carbon isotope ratios and source characterization of aerosols in ambient PM2.5 from the Indian COALESCE network - Debajyoti Paul; Gyanesh Kumar Singh; Tarun Gupta; Abhijit Chatterjee; Binoy K Saikia; Ramya Sunder Raman; Gazala Habib; Harish Phuleria; Chandra Venkataraman (Scientific Reports)
Abstract This study explores the potential of stable carbon isotope (δ 13C) composition of ambient carbonaceous aerosols in assessing the nature and apportionment of their sources. As part of the CarbOnaceous AerosoL Emissions, Source apportionment & ClimatE Impacts (COALESCE) network, δ 13C measurements (n = 1120) were conducted on aerosol samples collected from eight key locations spread across India. The δ 13C values of aerosols exhibit distinct spatial/temporal isotopic variabilities between background and polluted (urban) sites, and indicate an origin primarily from C3-biomass, fossil fuels, vehicular emission sources, etc. Spatial δ 13C distribution over India shows more negative δ 13C values in all seasons at the north Indian Himalayan (Kashmir) and east Indian sites (Jorhat) compared to other locations, implying that anthropogenic inputs contribute to more isotopic variability and a typical 13C-rich signature. Our study shows that although δ 13C provides qualitative information on source characteristics, it is not a robust standalone proxy for such applications. We conclude that δ 13C of aerosols could be a robust proxy for quantification studies if the extent of isotopic fractionation involved during aerosol formation/transport processes is well known and if it is assessed with one or more chemical markers like radiocarbon (Δ14C), trace elements/organic species, and specific biomarkers (e.g., levoglucosan or K+  BB).